Knowlege sharing initiative among public officers in Malaysia : the relationship between organizational factors and the quality of knowledge sharing / Zawiyah Mohd Yusof - Mohd Yusof, Zawiyah (Faculty of Information Management, 2014)
Knowledge sharing is one of the important dimensions in knowledge management. Previous studies capture many factors which influence knowledge sharing behaviour in organization be it from individual, organizational or technological perspective. Most studies emphasised on knowledge sharing practise rather than the quality of the endeavour. This study seeks to investigate the relationship between organizational factors (i.e. organizational culture, organizational structure, rewards and recognitions, office layout) and knowledge sharing quality in Malaysian public sector. A survey on 428 government officers in three selected government agencies was conducted employing questionnaires as the instrument for collecting data. The data was analysed using SPSS version 16.0. Factor analysis and reliability test were conducted to ensure the validity and reliability of the instrument. Confirmatory factor analysis was carried out to verify the existence of four dimensions of organizational factors. The results from correlation analysis indicate positive and significant correlation between organizational factors and knowledge sharing quality. However, multiple regression analysis shows significant relationship only exists for organizational culture. This indicates that knowledge sharing quality among Malaysian government officers is influenced by the culture of their organization.